Optimized ERICA engine intake wind tunnel test - Gibertini, G.; Auteri, F.; Colaiuda, L.; Ermacora, M.; Grassi, D.; Zanotti, A. (My University, 2015)
The present paper describes the experimental set up of the wind tunnel activity to assess the effectiveness of the CFD-based air-intake shape optimisation of the European platform tilt-rotor (ERICA). The wind tunnel campaign is carried out in the framework of the CleanSky TETRA project. The wind tunnel model was appositely designed and manufactured including the nacelle, the external wing and two interchangeable internal ducts (original and optimized). The performance evaluation is then made by the comparison of the pressure losses over the duct and the flow behavior at the engine face for both original and optimized intake duct shapes. Moreover, the evaluation of the internal flow field is made by means of an endoscopic PIV measurements performed in critical regions.
Keywords: Green Rotorcraft